Design of a high power combiner in HF band - Trình, Thăng; Tran Trong Hanh; Nguyen The Duy (Journal of Military Science and Technology, 2024)
Power combiners are commonly used in power amplifiers to achieve high power, especially in long-range and medium-range wireless communication device transmission systems. This paper proposes designing and implementing a high-power two-way power combiner operating in the HF (High Frequency) band, aiming to achieve an output power of over 1 kW. The power combiner is designed, implemented, and tested in the laboratory with the following achieved parameters: insertion loss between output and input better than 3.4 dB and isolation between inputs better than 26 dB. The experimental results showed that the proposed power combiner had better performance than existing combiners on the market. Mainly, power combining efficiency is over 88%, the standing wave ratio at ports is less than 1.25, and the operating temperature of the power combiner is less than 50 °C, meeting the set requirements.